Perubahan Kebijakan Amerika Serikat Terhadap Irak Pada Executive Order 13780 - Muslima Diputri, Kireina Lucretia; Fasisaka, Idin; Widya Nugraha, A. A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research aims to describe the United State of America's national interest to change their foreign policy regarding the United State of America's decision to remove Iraq from the travel ban. This research uses a descriptive qualitative method, and literature sources to collect the data. The data be analyzed uses two main concepts, which are national interest and foreign policy concepts. The results of this research are the United State of America has a defense interest with Iraq. Furthermore, the response from the Department of Defense for domestic factors, and the cooperative attitude by Iraq to answer the former executive order as an external factor as affecting the United State of America's foreign policy changed. Iraq removed from the travel ban also has fulfilled the first national vital interest of the United States of America, and expected could maintain the national security of the United State of America from terrorism. Key Words : United State of America, Iraq, Executive Order, National Interest, Foreign Policy changed